Madagascar Leaf-Tail Geckos (Uroplatus spp.) Share Independently Evolved Differentiated ZZ/ZW Sex Chromosomes - Pensabene, Eleonora; Yurchenko, Alona; Kratochvíl, Lukáš; Rovatsos, Michail (Cells, 2023)
Geckos are an excellent group to study the evolution of sex determination, as they possess a remarkable variability ranging from a complete absence of sex chromosomes to highly differentiated sex chromosomes. We explored sex determination in the Madagascar leaf-tail geckos of the genus Uroplatus. The cytogenetic analyses revealed highly heterochromatic W chromosomes in all three examined species (Uroplatus henkeli, U. alluaudi, U. sikorae). The comparative gene coverage analysis between sexes in U. henkeli uncovered an extensive Z-specific region, with a gene content shared with the chicken chromosomes 8, 20, 26 and 28. The genomic region homologous to chicken chromosome 28 has been independently co-opted for the role of sex chromosomes in several vertebrate lineages, including monitors, beaded lizards and monotremes, perhaps because it contains the amh gene, whose homologs were repeatedly recruited as a sex-determining locus. We demonstrate that all tested species of leaf-tail geckos share homologous sex chromosomes despite the differences in shape and size of their W chromosomes, which are not homologous to the sex chromosomes of other closely related genera. The rather old (at least 40 million years), highly differentiated sex chromosomes of Uroplatus geckos can serve as a great system to study the convergence of sex chromosomes evolved from the same genomic region.
Keywords: ještěři; pohlavní chromozomy; Lizards; genomics; Sex Chromosomes; Madagaskar; DNA-seq; sex chromosomes; cytogenetics; sex determination; qPCR; reptiles; Phylogeny; Animals; Madagascar; zvířata; evolution; fylogeneze